An affordable and adaptable Faraday isolator design for research - Nicholas L. Wong; Ben Delaney; Takanori Miyazaki; Emma Sokell; Fergal O’Reilly (HardwareX)
Presented here is an affordable Faraday isolator designed to account for conditions of high pulse energy and high total power lasers, with a clear input aperture allowing beam diameters up to 12 mm, and pulse energies and total powers limited by the dielectric crystal. This Faraday isolator is meant for laboratories with limited resources yet still need the features of commercial Faraday isolators. The design consists of a 3D printed mount housing seven permanent neodymium ring magnets, a Terbium Gallium Garnet (TGG) dielectric crystal, and two polarizing beam splitter cubes. Additionally, the design is customizable for different laser parameters, with the presented example isolator made for 1064 nm lasers. Measurements of the extinction ratio and a Stokes parameter analysis from different points within the isolator validated and characterized the constructed Faraday isolator. The final design had a measured minimum extinction ratio of 31.5±0.3 dB and a maximum of 39.9±0.2 dB depending on the polarization of back reflected light.